Parenting Style and Its Influence on Early Childhood Social Skills - Ayu, Sovia Mas; Dewi, Asmara; Ambar Wati, Regi Sintia; Mentari, Eca Gesang (Universitas Islam Negeri Raden Intan Lampung, 2023)
The family is the first environment that requires children to adjust well according to their age and maturity. Parents have a big role in influencing children's education in the family. What's happening in society lately is the lack of interaction between children and their peers. Children prefer to do things alone and lack sympathy for friends, so they no longer have sensitivity to their social environment. This study aimed to see how parenting influences the social skills of children aged 5–6 in the Banjit Village Market, Banjit District, Waykanan Regency, Indonesia. This research is quantitative. The population and research sample are parents in the Banjit Village Market with children aged 5-6. Data collecting instruments was a questionnaire distributed to parents. Before using the questionnaire instrument, it was first tested to determine its validity and reliability. The data analysis employed the simple linear regression test with the analysis requirements that have been done, including the normality test and linearity test. Based on the study results, parenting style (X) influences the social skills of children (Y) aged 5–6 at the Banjit Village Market, Banjit District, Waykanan Regency, Indonesia. This test is also strengthened by looking at the magnitude of the coefficient of determination (R square), which proves that parenting style influences children's social skills.